The Thin Illusion : Peran External Eating dan Tingkat Pendidikan terhadap Risiko Gangguan Makan - Aurelya, Annisa; Undarwati, Anna (Universitas Muhammadiyah Metro, 2025)
The risk of eating disorders is a growing mental health concern among adolescents and young adults. One factor believed to influence this risk is external eating, which refers to the tendency to eat in response to environmental cues such as the appearance or aroma of food. However, empirical findings have shown that the relationship between external eating and the risk of eating disorders is not always consistent and may be moderated by specific contextual variables, such as educational status. This study aimed to examine the influence of external eating and educational status, as well as their interaction, on the risk of eating disorders. A quantitative cross-sectional design was employed using General Linear Model (GLM) analysis on 190 participants (94 university students and 96 high school students). The instruments used were the Dutch Eating Behavior Questionnaire (DEBQ) and the Eating Attitudes Test-26 (EAT-26). The results showed that educational status had a significant effect on eating disorder risk (p = 0.043), as did the interaction between external eating and educational status (p = 0.037). However, external eating alone was not a significant predictor (p = 0.717). These findings indicate that the impact of external eating on eating disorder risk is contextual and influenced by educational factors. Therefore, preventive approaches to eating disorders should simultaneously consider both environmental and educational variables.